"The devil destroyed us": Satanism and gender violence in South Africa. Issue 3 (4th May 2017) - Falkof, Nicky
Abstract: In October 2011, a young South African woman named Kirsty Theologo was set on fire and left for dead by a group of her high school contemporaries in Linmeyer, Johannesburg. The killing was defined as a "Satanist murder, " leading to media, judicial, and religious interventions aimed at countering the apparent Satanic threat. This article examines press material surrounding Kirsty Theologo's death and the subsequent arrest and trial of her killers. It argues that the ongoing moral panic around Satanism in contemporary South Africa has obscured the often gendered nature of so-called satanic violence, showing the way in which the murder was instead placed within a familiar framework of Satanic panic in an act of collective displacement that elided the structural and historical contexts of acts of extreme violence perpetrated by young South African men on the bodies of young South African women.